2023
DOI: 10.7759/cureus.40170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Dry Eye Disease Among Children and Adults in Saudi Arabia: A Cross-Sectional Study

Dana A Alrabghi,
Rahaf L Abudungor,
Yasmeen S Alsulaiman
et al.

Abstract: Background: Dry eye disease (DED) is characterized by loss of homeostasis of the tear film or failure to produce sufficient amounts of tears to moisturize the eyes. The condition has been associated with several preventable risk factors.Objective: The objective of this study is to calculate the prevalence of dry eye and determine the associated risk factors among adults and children in Saudi Arabia.Methods: This is a cross-sectional study targeting all Saudi populations, including all the regions of Saudi Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…Using the OSDI questionnaire, the prevalence of DED in this study was 74.6%, consisting of mild (21.1%), moderate (14.9%), and severe (38.6%) levels (mean OSDI score: 30.4; SD 23.6). Consistent with our findings, a study published by Alrabghi et al [29] found a prevalence of DED of 74.9%, with severe cases detected in 30.4%. This has been corroborated by the study of Choi et al [30], with a prevalence of 78.1%, compromising mild, moderate, and severe cases detected in 25.8%, 18.7%, and 33.5%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using the OSDI questionnaire, the prevalence of DED in this study was 74.6%, consisting of mild (21.1%), moderate (14.9%), and severe (38.6%) levels (mean OSDI score: 30.4; SD 23.6). Consistent with our findings, a study published by Alrabghi et al [29] found a prevalence of DED of 74.9%, with severe cases detected in 30.4%. This has been corroborated by the study of Choi et al [30], with a prevalence of 78.1%, compromising mild, moderate, and severe cases detected in 25.8%, 18.7%, and 33.5%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The behavior when using DD could increase the DED-related symptoms such that the longer the use of DD, the greater the risk for DED symptoms. Consistent with this scenario, several studies documented an association between prolonged use of electronic devices and DED [29,30,32,36,37]. However, this is not the case in a study by Aljammaz et al [38], as they found no significant association between DED and the number of hours in front of the screen device, along with age, family history of DED, and history of corrective eye surgery.…”
Section: Discussionmentioning
confidence: 92%
“…Recent papers comparing these two questionnaires (OSDI and DEQ-5) reported a correlation of 0.649 in a population of 392 in Ghana (but over one-third were asymptomatic of dry eye) [ 21 ], and a correlation of 0.566 in a population of 101 in India [ 22 ]. This leads to uncertainty in this element of dry eye disease diagnosis in some patients [ 23 , 24 ]. The Symptom Assessment iN Dry Eye (SANDE) questionnaire, with its global assessment of dry eye frequency and severity reported on a visual analogue scale, also provides a sensitive (68%) and specific (94%) test in combination with non-invasive tear breakup time as an alternative to assessing the full TFOS DEWS II recommended diagnosis of dry eye disease [ 25 ].…”
Section: Introductionmentioning
confidence: 99%